Clinical and genetic study of a family with a paternally inherited 15q11–q13 duplication. Issue 6 (30th April 2013) - Marini, Carla; Cecconi, Antonella; Contini, Elisa; Pantaleo, Marilena; Metitieri, Tiziana; Guarducci, Silvia; Giglio, Sabrina; Guerrini, Renzo; Genuardi, Maurizio
Abstract Interstitial chromosome 15q11–q13 duplications are associated with developmental delay, behavioral problems and additional manifestations, including epilepsy. In most affected individuals the duplicated chromosome is maternally derived, whereas paternal inheritance is more often associated with a normal phenotype. Seizures have not been described in patients with paternal dup 15q11–q13. We describe a family with five individuals in three generations with a paternally‐inherited 15q11–q13 duplication, four of whom exhibited abnormal phenotypic characteristics, including seizures. The 18‐year‐old female proband presented with moderate intellectual disability, obesity, and epilepsy. Her brother manifested learning disability and behavioral problems. They both inherited the 15q11–q13 dup from their father who had a normal phenotype. Their paternal uncle and grandfather also had the duplication and were reported to have had seizures. Array‐CGH and MLPA analyses showed that the duplication included the TUBGCP5, CYFIP1, MKRN3, MAGEL2, NDN, SNRPN, UBE3A, ATP10A, GABRB3, GABRA5, GABRG3, and OCA2 genes. This report provides evidence for intrafamilial phenotypic variability of paternal dup 15q11–q13, ranging from normal to intellectual disability and seizures, and potentially expanding the phenotype of paternal 15q11–q13 interstitial duplications. © 2013 Wiley Periodicals, Inc.